Synthesis and Evaluation of Anti-HIV Activity of Mono- and Di-Substituted Phosphonamidate Conjugates of Tenofovir - Aaminat Qureshi; Louise A. Ouattara; Naglaa Salem El-Sayed; Amita Verma; Gustavo F. Doncel; Muhammad Iqbal Choudhary; Hina Siddiqui; Keykavous Parang (Molecules, 2022)
The activity of nucleoside and nucleotide analogs as antiviral agents requires phosphorylation by endogenous enzymes. Phosphate-substituted analogs have low bioavailability due to the presence of ionizable negatively-charged groups. To circumvent these limitations, several prodrug approaches have been proposed. Herein, we hypothesized that the conjugation or combination of the lipophilic amide bond with nucleotide-based tenofovir (TFV) (1) could improve the anti-HIV activity. During the current study, the hydroxyl group of phosphonates in TFV was conjugated with the amino group of L-alanine, L-leucine, L-valine, and glycine amino acids and other long fatty ester hydrocarbon chains to synthesize 43 derivatives. Several classes of derivatives were synthesized. The synthesized compounds were characterized by 1H NMR, IR, UV, and mass spectrometry. In addition, several of the synthesized compounds were evaluated as racemic mixtures for anti-HIV activity in vitro in a single round infection assay using TZM-bl cells at 100 ng/mL. TFV (1) was used as a positive control and inhibited HIV infection by 35%. Among all the evaluated compounds, the disubstituted heptanolyl ester alanine phosphonamidate with naphthol oleate (69), pentanolyl ester alanine phosphonamidate with phenol oleate (62), and butanolyl ester alanine phosphonamidate with naphthol oleate (87) ester conjugates of TFV were more potent than parent drug TFV with 79.0%, 76.5%, 71.5% inhibition, respectively, at 100 ng/mL. Furthermore, two fatty acyl amide conjugates of tenofovir alafenamide (TAF) were synthesized and evaluated for comparative studies with TAF and TFV conjugates. Tetradecanoyl TAF conjugate 95 inhibited HIV infection by 99.6% at 100 ng/mL and showed comparable activity to TAF (97–99% inhibition) at 10–100 ng/mL but was more potent than TAF when compared at molar concentration.